Use of Excel to Assist in Preparing Financial Reports: A Case Study at Pesantren Mamba'ul Hisan Assu'udiyah Pekalongan - Taufiq , Ahmad; Moenadhifah, Moenadhifah (Dharmahita: Journal of Community Service and Development, 2024)
In the era of globalization, knowledge in information technology is essential. This study explores the use of Excel to assist in preparing financial reports at the Mamba'ul Hisan Assu'udiyah Tirto Pekalongan Islamic Boarding School. The administration department, crucial for the institution's educational services, often faces challenges in managing administrative tasks effectively. By utilizing Microsoft Excel, financial reports can be generated more efficiently, streamlining processes from journal entries to simple financial statements. This research provides training on using Excel for financial reporting to enhance administrative performance. Findings indicate that well-structured financial reports, created with consistent and periodic record-keeping, significantly aid in decision-making and provide a clear overview of financial performance. The study concludes that using Excel facilitates the preparation of accurate financial reports, helping the institution avoid difficulties in collaborations with external parties. The research also highlights the simplicity and effectiveness of Excel as a tool for financial management, though it notes limitations in the scope of financial report examples provided.